Arbitrase Islam Dalam Perspektif Syariat Islam - Pratiwi, Dian; Aminin, Risti; Winario, Mohd (EL-EMIR Institute, 2024)
This article aims to find out about Islamic Arbitration in order to hand over the resolution of their disputes to a neutral and trusted third party, called an arbitrator or hakam. The arbitrator will then decide the case based on Islamic law (shariah) and justice. The method used in this research uses literature and library analysis. The research results show that Islamic Arbitration is an alternative dispute resolution that is in accordance with Islamic law. Islamic arbitration can be the right choice to resolve various types of disputes, including commercial disputes, family disputes, and inheritance disputes. However, it is important to note that Islamic arbitration is only binding on parties who have agreed to use it.